Assessment of autonomic functions and its association with telomerase level, oxidative stress and inflammation in complete glycemic spectrum– an exploratory study. Issue 2 (March 2019) - Sharma, Vivek Kumar; Savitha, S.; Vinod, Kolar Viswanath; Rajappa, Medha; Subramanian, Senthil Kumar; Rajendran, Rajathi
Abstract: Aims: In the present study we intended to study autonomic functions and its association with telomerase level, oxidative stress and inflammation in complete glycemic spectrum. Materials and methods: Age, gender and BMI matched 28 subjects in the age group of 25–50 years were recruited across complete glycemic spectrum as follows: 1) Normoglycemics (controls) 2) Prediabetics and 3) Frank diabetics. We assessed heart rate variability, cardiac autonomic function, lipid profile, adiponectin, malondialdehyde and telomerase level. Results: Time domain parameters and frequency domain parameters were significantly lower, and LFnu and LF/HF ratio were significantly higher in prediabetes and diabetes than control. Serum Adiponectin and HDL levels were significantly lower in diabetes than prediabetes and control, and prediabetes had significantly lower HDL than controls. Other lipid profile parameters (TC, TG, VLDL, LDL, non-HDL & derived lipid parameters were significantly higher in diabetes than prediabetes and control and prediabetes had significantly higher values than controls. MDA levels were significantly higher and TAS was significantly lower in diabetics than prediabetics and control group. Telomerase level was significantly higher in diabetes as compared to prediabetes and control. Telomerase had significantly negative correlation with SDNN, HF, TP, HDL and adiponectin, and significant positive correlation with MDA, fasting insulin, HOMA IR, TC, and AIP. Conclusion: Oxidative damage, inflammation and autonomic dysregulation may be involved in Telomere/Telomerase dysregulation in diabetes and telomerase levels can be used as a cardio-metabolic marker of diabetes.